Learning Opportunities in Biology Teacher Education Contribute to Understanding of Nature of Science - Till Bruckermann; Fridtjof Ochsen; Daniela Mahler (MDPI AG, 2018)
In order to educate scientifically literate children, teachers are required to include nature of science (NOS) in their classroom practice. However, as biology teachers’ own understanding of NOS is limited, promoting an initial understanding of NOS in teacher education is crucial. The aim of this study is to elucidate the importance of the first phase of teacher education for biology teachers’ understanding of NOS. More precisely, the study aims to examine the relationship between institutional determinants (e.g., the type of teacher education programme) and learning opportunities for pre-service biology teachers’ understanding of NOS. Pre-service biology teachers (N = 232) participated in a cross-sectional testing. The corresponding descriptions of N = 649 modules of biology teacher education from 20 German universities were analysed. Qualitative and quantitative methods were applied to relate the institutional determinants and the individual amount of learning opportunities to pre-service biology teachers’ understanding of NOS. Results reveal that both institutional determinants as well as the amount of learning opportunities are related to pre-service biology teachers’ understanding of NOS. This indicates that teacher education at university represents an important phase for biology teachers’ understanding of NOS. The results are discussed in terms of consequences for further research and teacher education.